2020
DOI: 10.1093/rheumatology/keaa655
|View full text |Cite
|
Sign up to set email alerts
|

Response to placebo in non-renal, non-neuropsychiatric systemic lupus erythematosus: a systematic review and pooled analysis

Abstract: Objectives Most randomized controlled trials (RCTs) in SLE have failed to reach their respective end points, with the rates of response to placebo (plus standard-of-care treatment) being unexpectedly high. The aim of this systematic review was to quantify the response to placebo in non-renal, non-neuropsychiatric lupus. Methods The PubMed database was searched (from 2000 to December 2019) for phase II/III RCTs assessing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The rate of mSRI attainment at 1 year in our study was 56%. In comparison, typical SRI response rates in recent clinical trials have ranged from 32% to 48% in the placebo (i.e., standard of care) arms (35), with these lower rates most likely reflecting the restrictions on concomitant medications such as glucocorticoid bursts applied in a trial setting and potential differences in an RCT population compared to an unselected observational cohort. We also examined persistence of mSRI attainment (relative to the baseline active disease visit for each patient) over up to 5 years of follow‐up, and found that 71–75% of mSRI responders at 1 year continued to meet the responder definition at subsequent annual time points.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of mSRI attainment at 1 year in our study was 56%. In comparison, typical SRI response rates in recent clinical trials have ranged from 32% to 48% in the placebo (i.e., standard of care) arms (35), with these lower rates most likely reflecting the restrictions on concomitant medications such as glucocorticoid bursts applied in a trial setting and potential differences in an RCT population compared to an unselected observational cohort. We also examined persistence of mSRI attainment (relative to the baseline active disease visit for each patient) over up to 5 years of follow‐up, and found that 71–75% of mSRI responders at 1 year continued to meet the responder definition at subsequent annual time points.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few years ago, the therapeutic armamentarium for SLE included GCs, antimalarials, traditional immunosuppressive drugs and few biological drugs. These drugs are valuable aids in achieving targets; of note is how the response to placebo (plus standard of care) is above 36% for all primary endpoints in non-renal, non-neuropsychiatric SLE RCTs [67]. However, reaching therapeutic targets remains an unmet need in a considerable proportion of patients, highlighting the importance of developing new drugs that improve the disease outcomes.…”
Section: Do Available Therapies Help In Achieving Targets?mentioning
confidence: 99%